2016
DOI: 10.1371/journal.pone.0147266
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electroencephalography Source Localization Algorithms with Multiple Cortical Sources

Abstract: BackgroundSource localization algorithms often show multiple active cortical areas as the source of electroencephalography (EEG). Yet, there is little data quantifying the accuracy of these results. In this paper, the performance of current source density source localization algorithms for the detection of multiple cortical sources of EEG data has been characterized.MethodsEEG data were generated by simulating multiple cortical sources (2–4) with the same strength or two sources with relative strength ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 32 publications
3
58
0
2
Order By: Relevance
“…Another crucial methodological decision was choice of methods used to compare different algorithms. Previous studies have compared algorithms for source localization -identifying the origin of a small number of sources (Bai et al, 2007;Hassan et al, 2014;Bradley et al, 2016;Finger et al, 2016;Barzegaran and Knyazeva, 2017;Hassan et al, 2017;Hincapié et al, 2017;Bonaiuto et al, 2018;Pascual-Marqui et al, 2018;Seeland et al, 2018;Anzolin et al, 2019;Halder et al, 2019), such as known networks during task or simulated dipoles. These methods are not directly generalizable to resting-state data, where activity is not a point source but is distributed widely across the cortex.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another crucial methodological decision was choice of methods used to compare different algorithms. Previous studies have compared algorithms for source localization -identifying the origin of a small number of sources (Bai et al, 2007;Hassan et al, 2014;Bradley et al, 2016;Finger et al, 2016;Barzegaran and Knyazeva, 2017;Hassan et al, 2017;Hincapié et al, 2017;Bonaiuto et al, 2018;Pascual-Marqui et al, 2018;Seeland et al, 2018;Anzolin et al, 2019;Halder et al, 2019), such as known networks during task or simulated dipoles. These methods are not directly generalizable to resting-state data, where activity is not a point source but is distributed widely across the cortex.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…We are not attempting to quantify the difference in peak activation of the estimate given a single 'true' active dipole as in simulation or theoretical studies (Pascual-Marqui, 2007;Barzegaran and Knyazeva, 2017;Pascual-Marqui et al, 2018;Halder et al, 2019), because of the expected cross talk from distributed sources in resting-state data. As a result, 'true' activity at a certain location does not necessarily imply a peak of estimated activity at that location -for example, localization statistics based on peak activation for sLORETA are accurate for single dipole localization, but are imperfect for localizing multiple dipoles (Bradley et al, 2016). The LE statistic used in this study is therefore more properly interpreted as follows: given true activity at a dipole, that activity will most strongly influence dipoles approximately LE mm from the true source on average, regardless of activity at other locations.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used Talairach Client toolbox 1 to identify the nearby cortex for each dipole. Afterwards, we visually examined all components to further reject the components with the dipoles located in the deep brain areas, since previous studies indicated the difficulty of localizing a deep source from the scalp EEG (Yao and Dewald, 2005; Bradley et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…EEG is inherently limited in its spatial resolution, particularly in comparison to fMRI. However, using our high-density EEG setup, along with the sLORETA inverse calculation based on subjectspecific boundary element models created with individual's anatomical MRI, we have demonstrated a resolution of roughly 5 mm 79,80 . This is suitable for distinguishing primary sensorimotor cortex and secondary motor areas as investigated here in our topographical analysis and allowed us to investigate multi-joint movements which would have been impractical inside an MRI scanner.…”
Section: Limitationsmentioning
confidence: 99%